Cultural Studies of Television Advertisements: An Analysis Based on Stuart Hall's Circuit of Culture and Roland Barthes' Semiotics - Rayhan, Muhammad (Indonesian Journal of Applied Linguistics Review, 2025)
This research aims to analyze the “AQUA 100% Murni Air Mineral Pegunungan” television commercial through Stuart Hall's Circuit of Culture approach, which consists of five main elements: representation, identity, production, consumption, and regulation. In addition to revealing the layers of meaning in the visual and verbal messages conveyed, this research also utilizes Roland Barthes' semiotic theory, specifically related to denotative, connotative, and mythical meanings. The method used is qualitative content analysis of the transcript of the ad video text uploaded on SehatAQUA's official YouTube channel. The results show that the advertisement represents mineral water as a symbol of health, freshness, and an active lifestyle that is harmonious with nature. Consumer identity is formed as a modern individual who cares about health and the environment. Ad production reflects a marketing strategy that is tailored to local values and the aspirations of urban communities. Consumption shows the negotiation of meanings by audiences based on their respective socio-cultural backgrounds, while regulations influence the limits of the content and presentation of advertising messages. This study concludes that television advertising acts not only as a promotional tool but also as a cultural medium that shapes values, identities, and consumption practices in contemporary society.